Factors Associated with STI Risky Sexual Behavior in Street Punk Children - Ratri Kartikasasmi; Zahroh Shaluhiyah; Bagoes Widjanarko (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the factors associated with STI-risk sexual behavior among street children in Batang District, Pemalang District, Pekalongan District, and Pekalongan City. The method used is quantitative research with a cross-sectional research design. The results showed that 62% of street punk children had STI-risk sex, and 58% did not have STI-risk sex. The bivariate analysis results showed no relationship between sex and recent education and sexual risk behavior for STIs. Still, there was a relationship between health risk behavior (drinking and drug use) and sexual risk behavior for STIs. In conclusion, gender and recent education were not significantly related to STI-risk sexual behavior. Still, health-risk behavior was significantly associated with STI-risk sexual behavior in street punk children. Keywords: Street Punk Children, Sexually Transmitted Infections, Risky Sexual Behavior